1999
DOI: 10.1152/ajpregu.1999.276.6.r1805
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic and cardiorespiratory responses to hypoxia in fetal sheep: adenosine receptor blockade

Abstract: 8-Phenyltheophylline (PT), a potent and specific inhibitor of adenosine receptors, was infused intra-arterially into unanesthetized fetal sheep to determine the role of adenosine in hypoxic inhibition of fetal breathing. PT in normoxic fetuses increased heart rate and the incidence of low-voltage electrocortical activity, rapid eye movements (REM), and breathing. Mean breath amplitude increased by 44%. Hypoxia (preductal arterial[Formula: see text] = 14 Torr) induced a metabolic acidemia, a transient bradycard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 26 publications
1
10
0
Order By: Relevance
“…In this study the ADO A 2A receptor antagonist abolished the hypoxia-induced rise in MAP, as previously reported for nonselective ADO receptor blockade (8,22). These results indicate that activation of ADO A 2A receptors is crucial to the increased peripheral resistance caused by acute reductions in fetal Pa O 2 .…”
Section: Arterial Pressuresupporting
confidence: 90%
See 1 more Smart Citation
“…In this study the ADO A 2A receptor antagonist abolished the hypoxia-induced rise in MAP, as previously reported for nonselective ADO receptor blockade (8,22). These results indicate that activation of ADO A 2A receptors is crucial to the increased peripheral resistance caused by acute reductions in fetal Pa O 2 .…”
Section: Arterial Pressuresupporting
confidence: 90%
“…The effects of hypoxia on MAP in fetal sheep depends on gestational age and the extent of O 2 deficiency. Hypoxia (⌬Pa O 2 of approximately Ϫ9 Torr), which generally has little effect on MAP in fetuses Ͻ0.85 term (6,27), produces a progressive increase in MAP in older fetuses (6,8,22). This hypertensive response presumably reflects the maturation of central or effector mechanisms rather than a change in hypoxic sensitivity of the carotid chemoreceptors (4).…”
Section: Arterial Pressurementioning
confidence: 99%
“…Several lines of evidence implicate adenosine as a mediator for hypoxia-induced depression of respiration. Hypoxic respiratory depression is reduced by the administration of adenosine receptor antagonists (Runold et al, 1989;Thomas and Marshall, 1994;Schmidt et al, 1995;Chau and Koos, 1999) or in mice lacking adenosine A 1 receptor (Johansson et al, 2001). During hypoxia, adenosine levels rise in the VLM in the cat (Richter et al, 1999).…”
Section: Release Of Atp In the Ventral Medulla During Hypoxia In Ratsmentioning
confidence: 99%
“…Adenosine has been implicated as a potential mediator (Runold et al, 1989;Thomas and Marshall, 1994;Schmidt et al, 1995;Chau and Koos, 1999;Johansson et al, 2001). However, we recently demonstrated that adenosine release in the medullary regions involved in respiratory control, nucleus tractus solitarii and rostral ventrolateral medulla (VLM), occurs too late to be responsible for the initiation of hypoxia-induced depression of the respiratory activity .…”
Section: Introductionmentioning
confidence: 99%
“…In vitro studies on hippocampal slices indicate that elevation of A1 receptors is associated with hypoxia (Jin and Fredholm, 1997), and severe asphyxia in vivo (Hunter et al, 2003c), following inhibition of neuronal activity. Studies in the fetal sheep further revealed that breathing movements can be inhibited by hypoxia and that such adaptation could be abolished by adenosine-receptor blockade at the level of the thalamus due to the inhibition of thalamic neurons (Chau and Koos, 1999). In a mouse knocked-out of A1 receptor, there is a significant decrease in tolerance to hypoxia (Johansson et al, 2001).…”
Section: Specific Roles Of A1 Receptor During Hypoxia Tolerancementioning
confidence: 99%